Prediagnostic use of estrogen-only therapy is associated with improved colorectal cancer survival in menopausal women: a Swedish population-based cohort study. (3rd July 2021) - Simin, Johanna; Liu, Qing; Wang, Xinchen; Fall, Katja; Williams, Cecilia; Callens, Steven; Engstrand, Lars; Brusselaers, Nele
Abstract: Background: Menopausal hormone therapy (MHT) reduces the risk of developing colorectal cancer (CRC), yet it is largely unclear whether it could also influence survival in women with CRC. Therefore, we aimed to investigate the influence of prediagnostic MHT use on CRC-specific and all-cause mortality in women with CRC. Methods: This nationwide nested cohort study, within a large population-based matched cohort, included all women diagnosed with incident CRC between January 2006 and December 2012 (N = 7814). A total of 1529 women had received at least one dispensed prescription of systemic MHT before CRC diagnosis, and 6285 CRC women with CRC did not receive MHT during the study period, as ascertained from the Swedish Prescribed Drug Registry. Multivariable Cox regression models provided adjusted hazard ratios (HRs) with 95% confidence intervals (CIs) for CRC-specific mortality and all-cause mortality. Results: Past use of prediagnostic estrogen-only therapy (E-MHT) was associated with lower CRC-specific (HR = 0.67, 95%CI 0.44–0.99) and all-cause mortality (HR = 0.68, 95%CI 0.59–0.93). However, all-cause mortality (HR = 1.23, 95%CI 1.02–1.48) was elevated among current prediagnostic E-MHT users who were 70+ years at diagnosis. Current estrogen combined progestin therapy (EP-MHT) was associated with higher CRC-specific mortality (HR = 1.61, 95%CI 1.06–2.44) in older women, but no association was shown for all-cause mortality. Conclusions: Our findings suggest that E-MHT, but not EP-MHT use, might be associated with improved CRC survival, indicating a potential role of estrogens in sex hormone-related cancers. However, association of MHT use with grade of cancer remains unclear.